Evaluation Of Finite Element Mesh Arrangements And Stress Intensity Factor Calculation Methods For Opening Mode Fracture Of Cracked-Cemented Materials - Pontjo Utomo; Hamid R. Nikraz (Institute of Research and Community Outreach - Petra Christian University, 2007)
Fracture mechanics is a branch of mechanics, which deals with the cracked body. Every construction material that currently in use inevitably is not flawless. The pre-existing crack may grow to cause structure failure due to low stress, which acts to a structure. Stress intensity factor (K) is a single parameter in fracture mechanics, which can be used to examine if a crack, would propagate in a cracked structure under particular loading condition. Finite element method is used to analyze the cracked body to provide the displacements data around the crack tip (at quarter point elements) due to load prescribed, for stress intensity factor determination. Two methods of stress intensity factor calculation, Quarter Point Displacement Technique (QPDT) and Displacement Correlation Technique (DCT), were evaluated. A series of standard fracture testing were undertaken to provide the fracture load data (Pf), which coupled with the stress intensity factor analytical formula to calculate fracture toughness. The results showed that under a particular mesh arrangement, the result of finite element analysis could deviate from the analytical formula calculation result. The QPDT method is suitable for compact tension specimen but DCT seemed to be not. For cracked beam analysis, the QPDT and DCT calculations were in good agreement with the analytical formula as long as coupled with the appropriate mesh arrangement around the crack tip.